Essay as the Autobiographical Heresy - Tomczok, Marta (Czytanie Literatury. Łódzkie Studia Literaturoznawcze, 2019)
This article discusses the special kind of Holocaust essay which, on the one hand, remains in opposition to academic texts and, on the other, is a text which resembles an autobiography, and which reveals its author’s personal engagement in the discussed problem. By analysing Jan Tomasz Gross’ study titled Ten jest z ojczyzny mojej..., ale go nie lubię and its consecutive printed versions, the author of this article discusses the benefit of engaging in essay-writing for the scholar, who fluctuates between the academic and non-academic discourses. To this end, she also discusses other Polish Holocaust essays published in the mid-1980s (by, e.g., Jan Błoński and Roman Zimand) and the theory of the essay by Theodor W. Adorno, which triggered Gross’ formal and notional search.